Au nanoparticle templated synthesis of pNIPAm nanogels - Singh, Neetu; Lyon, L. Andrew (Chemistry of Materials, 2007)

Bioconjugation of soft nanomaterials - Singh, Neetu; Blackburn, William H.; Lyon, L. Andrew (Biomedical Nanostructures, 2007)

Displacement-induced switching rates of bioresponsive hydrogel microlenses - Kim, Jongseong; Singh, Neetu; Lyon, L. Andrew (Chemistry of Materials, 2007)

Influence of ancillary binding and nonspecific adsorption on bioresponsive hydrogel microlenses - Kim, Jongseong; Singh, Neetu; Lyon, L. Andrew (Biomacromolecules, 2007)

Synthesis of multifunctional nanogels using a protected macromonomer approach - Singh, Neetu; Lyon, L. Andrew (Colloid and Polymer Science, 2008)

Functional delivery of siRNA in mice using dendriworms - Agrawal, Amit C.; Min, Dal-Hee; Singh, Neetu; Zhu, Haihao; Birjiniuk, Alona; von Maltzahn, Geoffrey; Harris, Todd J.; Xing, Deyin; Woolfenden, Stephen D.; Sharp, Phillip A.; Charest, Alain; Bhatia, Sangeeta N. (ACS Nano, 2009)

Responsive assemblies and microgel-based materials - Lyon, L. Andrew; Meng, Z.; Singh, Neetu; Sorrell, C. D.; John, A. (Chemical Society Reviews, 2009)

Chronic inflammatory responses to microgel-based implant coatings - Bridges, Amanda W.; Whitmire, Rachel E.; Singh, Neetu; Templeman, Kellie L.; Babensee, Julia E.; Lyon, L. Andrew; Garcia, Andres J. (Journal of Biomedical Materials Research, 2010)

Effect of nanoparticle conjugation on gene silencing by RNA interference - Singh, Neetu; Agrawal, Amit C.; Leung, Anthony K. L.; Sharp, Phillip A.; Bhatia, Sangeeta N. (Journal of American Chemical Society, 2010)

Bioresponsive mesoporous silica nanoparticles for triggered drug release - Singh, Neetu; Karambelkar, Amrita; Gu, Luo; Lin, Kevin; Miller, Jordan S.; Chen, Christopher S.; Sailor, Michael J.; Bhatia, Sangeeta N. (Journal of the Americal Chemical Society, 2011)

Nanoparticles that communicate in vivo to amplify tumour targeting - von Maltzahn, Geoffrey; Park, Ji-Ho; Lin, Kevin Y.; Singh, Neetu; Schwoeppe, Christian; Mesters, Rolf; Berdel, Wolfgang E.; Ruoslahti, Erkki; Sailor, Michael J.; Bhatia, Sangeeta N. (Nature Materials, 2011)

Controlling the cell adhesion property of silk films by graft polymerization - Dhyani, Vartika; Singh, Neetu (ACS Applied Materials & Interfaces, 2014)
We report here a graft polymerization method to improve the cell adhesion property of Bombyx mori silk fibroin films. B. mori silk has evolved as a promising material for tissue engineering because of its biocompatibility and biodegradability. However, silk's hydrophobic character makes cell adhesion and proliferation difficult. Also, the lack of sufficient reactive amino acid residues makes biofunctionalization via chemical modification challenging. Our study describes a simple method that provides increased chemical handles for tuning of the surface chemistry of regenerated silk films (SFs), thus allowing manipulation of their bioactivity. By grafting pAAc and pHEMA via plasma etching, we have increased carboxylic acid and hydroxyl groups on silk, respectively. These modifications allowed us to tune the hydrophilicity of SFs and provide functional groups for bioconjugation. Our strategy also allowed us to develop silk-based surface coatings, where spatial control over cell adhesion can be achieved. This control over cell adhesion in a particular region of the SFs is difficult to obtain via existing methods of modifying the silk fibroin instead of the SF surface. Thus, our strategy will be a valuable addition to the toolkit of biofunctionalization for enhancing SFs' tissue engineering applications.
Keywords: Bombyx mori; polymer grafting cell adhesion; silk films

Enhancing cubosome functionality by coating with a single layer of poly-epsilon-lysine - Deshpande, Sonal; Venugopal, Edakkal; Ramagiri, Shobha; Bellare, Jayesh R.; Kumaraswamy, Guruswamy; Singh, Neetu (ACS Applied Materials & Interfaces, 2014)
We report the preparation and characterization of monoolein cubosomes that can be easily surface modified through adsorption of a single layer of cationic poly-epsilon-lysine. Poly-epsilon-lysine coated cubosomes show remarkable stability in serum solution, are nontoxic and, are readily internalized by HeLa cells. The poly-epsilon-lysine coating provides chemical handles for further bioconjugation of the cubosome surface. We also demonstrate that the initial release rate of a hydrophilic drug, Naproxen sodium, from the cubosomes is retarded with just a single layer of polymer. Interestingly, cubosomes loaded with Naproxen sodium, recently shown to have anticancer properties, cause more apoptosis in HeLa cells when compared to free unencapsulated drug.
Keywords: bioconjugation; cubosomes; drug delivery vehicle; dual loading; theranostics

Mitigating the cytotoxicity of graphene quantum dots and enhancing their applications in bioimaging and drug delivery - Chandra, Anil; Deshpande, Sonal; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Singh, Neetu (ACS Macro Letters, 2014)
Despite the promising photophysical properties of fluorescent graphene quantum dots (GQDs), their cellular toxicity needs to be addressed before their full potential could be completely realized in biomedicine. A simple method for mitigating the toxicity of GQDs by embedding them in PEG matrix is reported here. The enhanced biocompatibility of polymer modified, P-GQDs, is attributed to reduced reactive oxygen species generation, as measured by an intracellular ROS assay. We also demonstrate the enhanced loading and efficient intracellular delivery of therapeutics by P-GQDs.

Construction and structural diversity of Cd-MOFs with pyrazole based flexible ligands and positional isomer of naphthalenedisulfonate - Singh, Udai P.; Singh, Neetu; Chandra, Suman (Inorganic Chemistry Communications, 2015)
In the present communication, we have reported the construction of a series of Cd(II)-MOFs using conformationally flexible ligand (CFL); 3,3',5,5'-tetramethy1-4,4'-bipyrazolyl (H(2)BPz), flexible bent ligand (FBL); methylenebis-(3,5-dimethylpyrazole) (H(2)MBPz) and positional isomer of naphthalene disulfonic acid salt ligands (1,5-NDS, 2,6-NDS). By using these ligands, four new coordination polymers namely [Cd(H(2)MBPz)(2) center dot 1,5-NDSA](n) (NDS-MOF-1), [Cd(H(2)BPz)center dot 1,5-NDSA](n) (NDS-MOF-2), {[Cd(H(2)MBPz)(2)](2+)center dot 2,6-NDSA(2-)}(n), (NDS-MOF-3) and {[Cd(H(2)BPz)(2)](2+).2,6-NDSA(n)(2-}) (NDS-MOF-4) have been synthesized. The crystal structure analysis revealed that the employment of positional isomeric naphthalene disulfonic acid salts resulted in different architectures ranging from one dimensional chain to two dimensional grid network and further connected into a three dimensional supramolecular structure through intermolecular hydrogen bonds, pi center dot center dot center dot pi and C-H center dot center dot center dot pi interactions. In addition, the photophysical properties and thermal stability studies for all the NDS-M0F5 1-4 were also investigated. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cadmium(II); Conformation; coordination polymers; Naphthalenedisulfonate; Photophysical properties; thermal stability

Bioinspired synthesis of bridged isochromane fused pyrazoles by a silver catalyzed cascade reaction and its application for antibacterial activity - Singh, Bhuvnesh; Tewari, Shreya; Kaur, Manleen; Sharma, Himanshu; Vanka, Kumar; Singh, Neetu; Singh, Ravi P. (JACS Au, 2025)
A stereoselective silver catalyzed one pot vinylogous aldol addition followed by a cascade [4+2] cycloaddition reaction of α-arylidene pyrazolinones to in situ generated isochromenylium ions has been developed, which provides an unprecedented bridged [2.2.2] [3.3.1] pentacyclic [5-6-6-6-6] skeleton consisting of an isochroman, chroman, and a pyrazole unit in one molecule with good to high yields as a single diastereomer. This method offers mild reaction conditions, wide substrate compatibility, excellent scalability and easy derivatization. A DFT study was carried out to clarify the reaction mechanism. It was exciting to observe that the unprecedented bridged isochromans synthesized here have shown excellent selectivity toward Gram-positive and Gram-negative bacteria. We demonstrate that while some structures are broad spectrum antibacterial there are two distinct structures that can be explored for selective activity.
Keywords: Antibacterial; Bridged [2.2.2] [3.3.1]; ROS; Stereoselective; Vinylogous aldol addition; [4+2] cycloaddition